The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/fbp.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

The kappa-opioid receptor agonist, nalfurafine, blocks acquisition of oxycodone self-administration and oxycodone’s conditioned rewarding effects in male rats

Abstract: Mu-opioid receptor (MOR) agonists are highly efficacious for the treatment of pain but have significant abuse liability. Recently, we reported that nalfurafine, when combined with oxycodone at a certain ratio, reduced the reinforcing effects of oxycodone in rats while producing additive antinociceptive effects. Questions remain, however, including if the combination will function as a reinforcer in drug-naïve rats, and if the combination produces aversive effects that could explain nalfurafine’s ability to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the KOR [ 35 S]­GTPγS binding assays, all compounds showed moderate-to-high efficacy with single- or double-digit nanomolar potencies (Table ). As KOR agonists may help treat morphine or oxycodone addiction and opioid-induced pruritus, , the partial agonism exhibited by these compounds on the KOR may in fact be beneficial in OUD treatments. On the other hand, the high potency and efficacy of compound 32 toward the KOR, which were not observed in the in vivo antinociception study, could be concerning clinically as a full KOR agonist could also elicit dysphoria and sedation .…”
Section: Resultsmentioning
confidence: 99%
“…In the KOR [ 35 S]­GTPγS binding assays, all compounds showed moderate-to-high efficacy with single- or double-digit nanomolar potencies (Table ). As KOR agonists may help treat morphine or oxycodone addiction and opioid-induced pruritus, , the partial agonism exhibited by these compounds on the KOR may in fact be beneficial in OUD treatments. On the other hand, the high potency and efficacy of compound 32 toward the KOR, which were not observed in the in vivo antinociception study, could be concerning clinically as a full KOR agonist could also elicit dysphoria and sedation .…”
Section: Resultsmentioning
confidence: 99%
“…Repeating what is observed in humans, preclinical reports have demonstrated that nalfurafine does not cause conditioned place aversion in mice (Liu et al, 2019). A series of studies showed that acute nalfurafine dose‐dependently suppresses morphine‐induced hyperlocomotion and that repeated nalfurafine treatment not only blocks naloxone‐precipitated withdrawal syndromes after chronic morphine treatment but also reduces morphine‐induced conditioned place preference as well as oxycodone‐induced conditioned place preference and self‐administration in rodents by activating κ receptor(Kaski et al, 2019; Tsuji et al, 2000; Zamarripa, Patel, et al, 2020; Y. Zhang & Kreek, 2020). However, under a drug‐versus‐food choice procedure, non‐contingent U50488 and nalfurafine administration decreases the number of choices made during the behavioural session without altering fentanyl choice in rats (Townsend, 2021),.…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
“…Nalfurafine (NLF), also known as TRK-820, was first synthesized by the Nagase lab in 1998 and was clinically approved in Japan as a second-line antipruritic to treat uremic pruritis in end-stage renal disease patients on hemodialysis in 2009 (Remitch 2.5 μg/day). Nalfurafine has additionally been studied for uremic pruritis in clinical trials which have thus far not yielded its approval in the United States. Prior to the discovery of its antipruritic indication, NLF was originally developed as an analgesic for postoperative pain and it exhibited antinociceptive activity in a variety of pain models. , While other KOR agonists have been limited by adverse side effects such as psychotomimesis, dysphoria, and sedation, NLF does not result in dysphoria or psychotomimesis at potential therapeutic doses. In general, it has been found that antinociceptive effects are produced at doses smaller than those that produce hypolocomotion, conditioned place aversion, and motor incoordination. ,, One suggested explanation for NLF’s lack of dysphoric properties is its potential as a biased KOR agonist with greater bias in humans than rodents, , but see also with further explorations. ,, This may be a dose/efficacy difference that has not been systematically studied as it has been with biased MOR agonists. Additionally, interpretational limits are presented by the methods used to calculate bias, e.g.…”
Section: Introductionmentioning
confidence: 99%